Respiratory Syncytial Virus (RSV) as a Secondary Diagnosis among Hospitalized Patients in Germany: Outcomes and Economic Burden - Markus Weinert; Jana Diekmannshemke; Kylie Braegelmann; Manuel Batram; Julian Witte; Stefan Scholz; Darshan Mehta; Bernhard Ultsch; Kristina Dobrindt; Jens Gottlieb (Infectious Diseases and Therapy)
Abstract Introduction Respiratory syncytial virus (RSV) is a pathogen that may cause severe respiratory infections. Recent research indicates that RSV may be underdiagnosed, especially in adult populations. This study aims to investigate the burden of RSV in hospitalized adults. Methods A retrospective, matched-control cohort study covering the seasons 2011/2012 to 2021/2022 was performed on the basis of anonymized claims data from 6 million individuals in multiple German statutory health funds. Analyses comprise hospitalized persons aged 18+ years. Patients with RSV were identified using the International Classification of Diseases, tenth revision, German Modification (ICD-10-GM) codes directly related to RSV (narrow approach) and indirectly related to RSV (ICD-10-GM codes covering lower respiratory tract infections, broad approach). Comparing these cohorts can provide a reasonable estimate of upper and lower bounds. For patients with a secondary inpatient diagnosis of RSV, we evaluated mortality rates, lengths of stay (LOS), costs, special fees, intensive care unit (ICU) admission rates, ventilation rates, and use of high-flow oxygen. Cohorts were matched with controls using an 1:1 exact matching approach using age, sex, Charlson Comorbidity Index (CCI, excluding age), main inpatient diagnosis, and quarter/year of admission. Results Mortality rates were between 15.5 (standard deviation, SD 1.031) and 19.8 (SD 0.070) times higher for patients with secondary inpatient diagnosis of RSV compared with their controls. Average LOS was 1.77 (SD 0.007) times longer than in controls, and healthcare costs were between 5600 EUR (SD 132.81) and 8400 EUR (SD 2313.54) higher for patients with RSV. No significant differences were found between patients with RSV and controls with respect to rehospitalization rate, invasive ventilation rate, or high-flow oxygen rate; however, patients indirectly related to RSV were admitted more often to intensive care (10.54% versus 3.25%). Conclusions Our study provides a deeper understanding of how RSV secondary diagnosis affects hospitalized patients, finding that RSV infection dramatically increases mortality rate, LOS, and inpatient healthcare costs. These findings support a broad RSV-vaccination recommendation for this patient group.